Standardisasi Halal dan Prosedur Sertifikasi Halal di Indonesia dan Thailand - ikhsan, ikhsan gasali; Supardin, Muhammad Ikhlas (el hisbah Journal of Islamic Economic Law, 2024)
The increase in tourists after Covid-19 has begun to be seen in several countries, this clearly affects the economic growth of tourist destination countries. Indonesia and Thailand are two countries that have shown significant development in terms of tourism. This study aims to examine the standards and methods of halal certification in tourist destination countries such as Indonesia and Thailand. This study uses a qualitative approach with a descriptive-comparative method. This approach was chosen to gain a deep understanding of the regulation of halal fatwas and the procedures for granting halal certification in Indonesia and Thailand. This study is library research, where data is collected through literature searches, documents. Data analysis is carried out descriptively-comparatively, namely by systematically describing the systems of each country, then comparing the legal structure, religious authority, and applicable certification mechanisms. The results of the study show that the executor of the task of inspecting halal food in Indonesia is the MUI through LPPOM-MUI. Furthermore, the government has established the Halal Product Assurance Organizing Agency (BPJPH) which is tasked with issuing halal certificates. On the other hand, Thailand has two institutions that focus on product halalness, namely the Halal Standards Institute of Thailand and the Halal Science Center of Chulalongkorn University (HSC-CU).